Organizations and unusual routines : a systems analysis of dysfunctional feedback processes - Rice, Ronald E. (Cambridge University Press, 2010)
"Everyone working in and with organizations will, from time to time, experience frustrations and problems when trying to accomplish tasks that are a required part of their role. This is an unusual routine - a recurrent interaction pattern in which someone encounters a problem when trying to accomplish normal activities by following standard organizational procedures and then becomes enmeshed in wasteful and even harmful subroutines while trying to resolve the initial problem. They are unusual because they are not intended or beneficial, and because they are generally pervasive but individually infrequent. They are routines because they become systematic as well as embedded in ordinary functions. Using a wide range of case studies and interdisciplinary research, this book provides researchers and practitioners with a new vocabulary for identifying, understanding, and dealing with this pervasive organizational phenomenon, in order to improve worker and customer satisfaction as well as organizational performance"--Provided by publisher